Cintadiri.Id : Pencegahan dan Penanganan Self-Harm Berbasis Sistem Informasi - Faradiba, Andi Tenri; Syihab, Aisyah; Arsad, Bambang Riono; Sumarno, Rahayu; Prameswari, Larashaty Putri; Aridin, Icha Puspita; Bintang, Arthan Laki; Wiraputra, Ayala Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Non-suicidal self-injury (NSSI) or self-harm is on the rise among Indonesian adolescents. As digital natives, they often turn to the internet for information, including mental health support. To address this issue, a team from the Faculty of Psychology and Informatics Engineering at Universitas Pancasila developed cintadiri.id, an information system designed to prevent and handle self-harm. The website offers a range of features, including psychoeducational articles, relaxation videos, a journaling tool, and consultations with psychologists. To evaluate the website's effectiveness, a survey was conducted among 30 participants aged 17-21. There are five questions given, such as